2015
DOI: 10.1371/journal.pone.0116799
|View full text |Cite
|
Sign up to set email alerts
|

Azilsartan Reduced TNF-α and IL-1β Levels, Increased IL-10 Levels and Upregulated VEGF, FGF, KGF, and TGF-α in an Oral Mucositis Model

Abstract: Oral mucositis (OM) is a common complication of treatments for head and neck cancer, particularly radiotherapy with or without chemotherapy. OM is characterised by oral erythema, ulceration, and pain. The aim of this study was to evaluate the effect of azilsartan (AZT), an angiotensin II receptor antagonist, on 5-fluorouracil (5-FU)-induced oral mucositis (OM) in Syrian hamsters. OM was induced by the intraperitoneal administration of 5-FU on experimental days 1 (60mg/Kg) and 2 (40mg/Kg). Animals were pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…Deficiency of TNF-α in a lung injury model was sufficient to prevent symptoms of radiation pneumonitis 70 . TNF-α has also been implicated in radiation mucositis, enteritis, and dermatitis 7175 . The clinical availability of agents targeting TNF-α to treat rheumatologic disorders provides a unique opportunity for clinical translation, and will likely enhance investigation into this molecule and its pathway.…”
Section: Tgf-β and Tnf-α Signaling In Normal Tissue Toxicitymentioning
confidence: 99%
“…Deficiency of TNF-α in a lung injury model was sufficient to prevent symptoms of radiation pneumonitis 70 . TNF-α has also been implicated in radiation mucositis, enteritis, and dermatitis 7175 . The clinical availability of agents targeting TNF-α to treat rheumatologic disorders provides a unique opportunity for clinical translation, and will likely enhance investigation into this molecule and its pathway.…”
Section: Tgf-β and Tnf-α Signaling In Normal Tissue Toxicitymentioning
confidence: 99%
“…It was found that the IL-10 levels in hamsters with 5-FU-induced OM were higher than those in healthy animals 27 . The use of COX-2 inhibitors and cys-LTs inhibitors (at doses of 10 and 20 mg/ kg/d for 10 d) also did not significantly reduce the expression of this cytokine.…”
Section: ■ Discussionmentioning
confidence: 91%
“…The OM model presents increased expression of TNF-α and IL1-β at its inflammatory peak (day 10) 13,[24][25][26][27][28] . The present study corroborates such results, demonstrating a significant increase in TNF-α and IL1-β expression in the positive (5-FU) control group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The tissue blocks were cut with 5-µm microtome, fixed, and stained on histological slides with dewaxing in xylol, hydration in alcohol baths (100% to 70%), stained with hematoxylin and eosin, dehydrated in alcohol baths (70% to 100%), clarified with xylol, and slides were assembled for analysis by light microscopy (40× Nikon E200 LED, São Paulo, Brazil). Oral mucosa were classified into score: Score 1: Normal epithelium and connective tissue without vasodilation, absent or discrete cellular infiltration, or absence of hemorrhagic areas, ulcerations, or abscesses; score 2: Discrete areas of vasodilation or re-epithelialization, slight inflammatory infiltration with mononuclear prevalence, and absence of hemorrhagic areas, edema, ulcerations, or abscesses; score 3: Moderate vasodilation, areas of epithelial degeneration, inflammatory infiltration with neutrophil prevalence, presence of hemorrhagic areas, edema, and eventual ulceration, and absence of abscesses; and score 4: Severe vasodilation and inflammatory infiltrate with neutrophils [26].…”
Section: Macroscopic and Histopathological Analysesmentioning
confidence: 99%
“…The plates were read at 490 nm by an ELISA plate reader (Polaris, Celer, Belo Horizonte, Brazil). To obtain the results in pg/mL, the standard curve was obtained according to the manufacturer's instructions for each antibody [24,26].…”
Section: Assays For Quantification Of Cytokines and Reduced Glutathiomentioning
confidence: 99%